Acquisition of Title to Territory in the Aftermath of the Use of Force in the United Nations Era: The case of the State of Israel - Soroczyński, Rafał (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2017)
The territory to which the State of Israel had a title as a newly-created state corresponded to the areas allotted to Jews by the provisions of the resolution 181(II) adopted by the General Assembly of the United Nations on November 29, 1947, which had recommended the partition of Palestine and creation of the Arab state, the Jewish state and the City of Jerusalem as a corpus separatum. As this territorial regime had been modified during the Arab-Israeli war of 1948-1949 and Israel’s government has recognized the areas seized by it during the war as part of its territorial domain, the problem arose as to Israel’s title to those additional territories situated between the 1947 partition lines and the lines established in accordance with the armistice agreements of 1949. Due to important characteristics of the legal status of former mandatory Palestine and to the fact that considerable parts thereof became occupied territories, the process of consolidation of the title thereto required the consent of the international community as a whole. This consent has in fact been granted, both by the international community and by representatives of Palestinian Arabs, in respect of large parts of territories situated between the 1947 partition lines and the 1949 armistice lines. There are no doubts that the State of Israel has sovereign, uncontested rights to these areas. As it constitutes important departure from the generally accepted principle that the use of force in any form cannot serve as a root of title to territory, this situation is of particular interest, providing support for the view that this principle cannot be analyzed without due regard paid to those exceptional situations where the international community decided to depart from its strict application in order to safeguard stability of territorial solutions.